A comparison of tournament systems for the men’s World Handball Championship - Donoghue Peter O’; Kristjánsdóttir Hafrún; Halldórsson Kristján; Þorgeirsson Sveinn (International Journal of Computer Science in Sport)
The men’s Handball World Championship commences with eight round robin groups of four teams before the “main round” of four groups of six teams. These groups of six each include the top three teams from pairs of initial groups. The tournament draw uses pots of eight which risks two teams in the top four appearing in the same group of the main round. A further issue is that teams finishing between third and sixth in the main round groups are awarded tournament places between ninth and 24th without any further matches. Therefore, the purpose of this investigation was to compare the current tournament system with alternatives using pots of four teams in the draw, and / or adding a knockout stage to place teams from ninth to 24th. These four tournament systems were simulated 100,000 times, using underlying regression models for the goals scored based on their World ranking points. Introducing pots of four increased the chance of reaching the quarter-finals for teams ranked one to four and nine to 12 by 1.3% and 1.6% respectively. It is recommended that the draw uses pots of four teams associated with pairs of initial groups that lead to common main draw groups.